APPLICATION OF MODERN INFORMATION TECHNOLOGY IN EDUCATION PROCESSES (Spectrum Journal of Innovation, Reforms and Development, 2023)
Information technology in education needs a culture. This culture needs to be learned along with the use of hardware resources. The system needs to be educated to use information technology; otherwise, purchase and transfer of technology and investment will be nothing but wasting resources. Although these technologies are not impartial in any sense they should be used as means for communicating information, in the existing social structures. However since the process of change and transformation is in the nature of human social institutions, the educational system is also prone to some alterations. But the fundamental problem is that what strategies should be adopted so that education systems in developing countries do not only follow developed countries but grow and progress base on their own needs in the path of progress. In this paper, after explanation about the role of information technology and its place in education in underdeveloped countries and Uzbekistan, a discussion is presented on how to enter the field of information society and how to use information technologies.